2015
DOI: 10.1073/pnas.1508465112
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen regulator GlnR controls uptake and utilization of non-phosphotransferase-system carbon sources in actinomycetes

Abstract: The regulatory mechanisms underlying the uptake and utilization of multiple types of carbohydrates in actinomycetes remain poorly understood. In this study, we show that GlnR (central regulator of nitrogen metabolism) serves as a universal regulator of nitrogen metabolism and plays an important, previously unknown role in controlling the transport of non-phosphotransferase-system (PTS) carbon sources in actinomycetes. It was observed that GlnR can directly interact with the promoters of most (13 of 20) carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 37 publications
4
80
0
Order By: Relevance
“…The regulation of starch utilization in soil microorganisms is under GlnR and PhoP control, indicating that nitrogen/ phosphate limitation triggers the PhoP-and GlnR-mediated response, resulting in the expression of nitrogen/phosphate-related genes, as well as genes involved in degradation and utilization of starch. Our previous work also found that GlnR exerts a regulatory effect on uptake and utilization of carbon sources in S. erythraea (36) and could influence production of acetyl coenzyme A (acetyl-CoA), as it directly regulated the transcription of three acs genes encoding acetyl-CoA synthetases (unpublished data). Why do nitrogen/phosphate-sensing regulators activate expression of the genes involved in transport and degradation of carbon sources, as well as acetyl-CoA synthesis?…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The regulation of starch utilization in soil microorganisms is under GlnR and PhoP control, indicating that nitrogen/ phosphate limitation triggers the PhoP-and GlnR-mediated response, resulting in the expression of nitrogen/phosphate-related genes, as well as genes involved in degradation and utilization of starch. Our previous work also found that GlnR exerts a regulatory effect on uptake and utilization of carbon sources in S. erythraea (36) and could influence production of acetyl coenzyme A (acetyl-CoA), as it directly regulated the transcription of three acs genes encoding acetyl-CoA synthetases (unpublished data). Why do nitrogen/phosphate-sensing regulators activate expression of the genes involved in transport and degradation of carbon sources, as well as acetyl-CoA synthesis?…”
Section: Discussionmentioning
confidence: 88%
“…(C and D) Curves of growth (C) and consumption of starch (D) of wt, ⌬glnR, ⌬glnR::glnR, wt::glnR, and wt::phoP strains grown in balanced Evans medium supplemented with 0.5% starch as the sole carbon source. Samples for growth and starch digestion curve analysis were harvested at nine time points (12,24,36,48,60,72,84,96, and 108 h). Data are representative of those from three independent biological replicates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the NlpR protein may be considered as a pleiotropic regulator since it can influence the expression of genes of multiple pathways. A similar behaviour have been reported for several other regulators in actinobacteria (Martín and Liras, ; Allenby et al ., ; Martín et al , ; Rabyk et al ., ; Liao et al ., ). In contrast to local specific regulators, global and pleiotropic regulators often possess more degenerate binding sites which provide them versatility in their binding affinity, as well as the possibility to control a higher number of genes.…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports have demonstrated that GlnR directly regulates the uptake and utilization of non-phosphotransferase system carbon sources in S. erythraea. The expression of most (13 of 20) carbohydrate ATP-binding cassette (ABC) transporters was activated by GlnR in response to nitrogen availability (12). Therefore, GlnR-mediated control of carbohydrate transport may be highly conserved among actinomycetes.…”
mentioning
confidence: 99%